2019
DOI: 10.1111/jam.14174
|View full text |Cite
|
Sign up to set email alerts
|

The composition and structure of the intestinal microflora of Anguilla marmorata at different growth rates: a deep sequencing study

Abstract: Aims The aim of this study was to determine the intestinal microflora of Anguilla marmorata at different growth rates and to identify potential probiotic/pernicious bacteria. Methods and Results Bacterial communities from eight different eels' intestinal sites (including the intestinal contents and the intestinal mucosa) from three fish groups (three fast‐, two medium‐, and three stunted‐growth samples), two water samples, and one diet sample were characterized by Illumina next‐generation sequencing. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 75 publications
(125 reference statements)
5
18
0
Order By: Relevance
“…The trillions of intestinal microbes harboured in the mammalian gut profoundly influences the host’s health and disease status (Vaarala ; Frese et al ; Lin et al ). An increasing number of studies have shown that the small intestinal microbiota has a profound impact on host metabolism and growth (El Aidy et al ; Burbach et al ; Li et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The trillions of intestinal microbes harboured in the mammalian gut profoundly influences the host’s health and disease status (Vaarala ; Frese et al ; Lin et al ). An increasing number of studies have shown that the small intestinal microbiota has a profound impact on host metabolism and growth (El Aidy et al ; Burbach et al ; Li et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Cetobacterium is the core flora in the intestinal tract of fish (Jiajia et al, 2012). It can produce acetic acid to promote protein synthesis or combine with coenzyme A to boost sugar and fat metabolism and can synthesize fats, carbohydrates, and proteins for the host's use (Lin et al, 2019). This suggests that Cetobacterium may play a vital role in the development and growth of fish.…”
Section: Discussionmentioning
confidence: 99%
“…The two groups of dominant symbiotic bacteria are Clostridium_sensu_stricto_1. It has the highest content in the healthy growth population and was the major member of intestinal bacteria in some fish (Sullam et al, 2012;Lopetuso et al, 2013;Lin et al, 2019). The abundance of Clostridium_sensu_stricto_1 in the intestine of healthy piglets is higher, and decrease in its abundance may cause diarrhea in healthy piglets (Han et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the intestinal microbiota of eels was not well studied, and only several studies were conducted to investigate the intestinal microbiota of different eel species, including the mucosal microbiota metagenome of European eels from five sources (Carda-Diéguez et al, 2014), intestinal microbiota compositions of Japanese eel (Anguilla japonica) (Lee et al, 2015), the compositions of the intestinal microbiota of three eel species (Anguilla japonica, A. marmorata, and A. bicolor pacifica) (Hsu et al, 2018), the community composition and complexity of the intestinal microbiota in cultivated European eels during three stages of their lifecycle (Huang et al, 2018), and composition and structure of the intestinal microflora of marbled eels at different growth rates (Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%